SIKAP PETANI TERHADAP PRODUK BANK SYARIAH MANDIRI DI KECAMATAN GUBUG KABUPATEN GROBOGAN - Sella Setya Sahanaya; Sriroso Satmoko; Tutik Dalmiyatun (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2020)
Bank was one of the important financial institutions in supporting economic growth, the bank was being an alternative source of capital for farmers to meet the needs of agricultural production facilities. This study aims to analyze the factors that influence the attitudes of farmers towards Bank Syariah Mandiri products, analyze the attitudes of farmers toward Bank Syariah Mandiri products, analyze the influence of factors that influence the attitudes of farmers including education, age duration of farming, number of family dependents and income towards Bank Syariah Mandiri products in Grobogan Regency Gubug District. The method used in this study is a survey method. The study was conducted on Juny 14-July 30, 2019 in Trisari Village, Gubug District, Grobogan Regency. Research location was chosen intentionally and the method of determining the number of samples used is purposive sampling with non-probability techniques. The number of respondents is 47 people from the Farmer Group Subur Makmur. Data analyzed with descriptive analysis to analyze the attitudes of farmers, and the factors forming farmers 'attitudes towards Bank Syariah Mandiri Products while the quantitative analysis was used to determine the effect of attitude forming factors with farmers' attitudes towards Bank Syariah Mandiri Products in the Gubug District using multiple linear regression. Farmer's attitude towards Bank Syariah Mandiri Products in the category good/like with a score of 77.78%. Based on the F test shows that simultaneously there is a significant influence between the age of the farmer, the length of farming, the level of education the number of family dependents, and the income of farmers' Attitudes towards Bank Mandiri Syariah Products in Grobogan District. The length of farming, and the number of family dependents partially do not affect the farmers' attitudes towards Bank Syariah Mandiri Products. Based on the t test, the results show that the age of the farmer, the level of education, and income partially influences the attitude of the Farmers towards Bank Syariah Mandiri Products. Keyword: attitude forming factors, Bank Syariah Mandiri products, attitudes of farmers.